2012
DOI: 10.4103/0970-9290.100449
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee propolis extract in periodontal treatment: A clinical and microbiological study of propolis in periodontal treatment

Abstract: Subgingival irrigation with propolis extract as an adjuvant to periodontal treatment was more effective than scaling and root planing as assessed by clinical and microbiological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 0 publications
6
62
0
4
Order By: Relevance
“…Recently, a study was conducted to explore the clinical and microbiological efficacy of propolis extract as a subgingival irrigant in periodontal treatment. It was concluded that subgingival irrigation with propolis extract can be considered as an adjuvant to SRP [15]. However, the effect of propolis as a local drug delivery agent in treatment of chronic periodontitis, in relation to the clinical and microbiological parameters has not been studied till date, according to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a study was conducted to explore the clinical and microbiological efficacy of propolis extract as a subgingival irrigant in periodontal treatment. It was concluded that subgingival irrigation with propolis extract can be considered as an adjuvant to SRP [15]. However, the effect of propolis as a local drug delivery agent in treatment of chronic periodontitis, in relation to the clinical and microbiological parameters has not been studied till date, according to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…Propolis has been used for the treatment of aphthous ulcers [12], candidiasis [13], gingivitis [14], periodontitis [15], and pulpitis [16]. Studies on propolis applications have increased because of its therapeutic and biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective flavonoids that act against bacteria are galangin, pinocembrin, pinostrobin. Other components that contribute to antibacterial action are ferulic and caffeic acids [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A irrigação com extrato de própolis subgengival após raspagem e alisamento radicular já demonstrou maior efetividade nos parâmetros clínicos e microbiológicos, com redução de Porphyromonas gingivalis (Dimov et al, 1992;Gebara et al, 2003;Coutinho, 2012). Entretanto, são escassos os estudos que utilizam metodologia radiográfica para avaliar o efeito da aplicação tópica de extrato de própolis como substância auxiliar no tratamento da DP.…”
Section: Introductionunclassified